Ultrasonographic Evaluation of Botulinum Toxin Injection Site for the Medial Approach to Tibialis Posterior Muscle in Chronic Stroke Patients with Spastic Equinovarus Foot: An Observational Study - Picelli, Alessandro (Toxins (Basel), 2017)
The tibialis posterior muscle is a frequent target for injection of botulinum toxin during the management of spastic equinovarus foot in adults with post-stroke spasticity. Although it is deep-seated, the needle insertion into the tibialis posterior muscle is usually performed using anatomical landmarks and safety information obtained from healthy subjects and cadavers. Our aim was to evaluate the botulinum toxin injection site for the medial approach to the tibialis posterior muscle in chronic stroke patients with spastic equinovarus foot. Forty-six patients were evaluated at the affected middle lower leg medial surface with ultrasonography according to the following parameters: tibialis posterior muscle depth, thickness, and echo intensity. As to the spastic tibialis posterior, we found a mean muscle depth of 26.5 mm and a mean muscle thickness of 10.1 mm. Furthermore we observed a median tibialis posterior muscle echo intensity of 3.00 on the Heckmatt scale. The tibialis posterior muscle thickness was found to be inversely associated with its depth (p < 0.001) and echo intensity (p = 0.006). Furthermore, tibialis posterior muscle depth was found to be directly associated with its echo intensity (p = 0.004). Our findings may usefully inform manual needle placement into the tibialis posterior for the botulinum toxin treatment of spastic equinovarus foot in chronic stroke patients.